1989
DOI: 10.1038/340245a0
|View full text |Cite
|
Sign up to set email alerts
|

A novel genetic system to detect protein–protein interactions

Abstract: Protein-protein interactions between two proteins have generally been studied using biochemical techniques such as crosslinking, co-immunoprecipitation and co-fractionation by chromatography. We have generated a novel genetic system to study these interactions by taking advantage of the properties of the GAL4 protein of the yeast Saccharomyces cerevisiae. This protein is a transcriptional activator required for the expression of genes encoding enzymes of galactose utilization. It consists of two separable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
3,466
0
34

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,522 publications
(3,559 citation statements)
references
References 17 publications
22
3,466
0
34
Order By: Relevance
“…As an approach to identify molecules that are involved in Tek signaling pathways, we have used the yeast twohybrid system to ®nd proteins that can interact with the intracellular domain of Tek in a phosphotyrosinedependent manner (Fields and Song, 1989;Chien et al, 1991;O'Neill et al, 1994;Pandey et al, 1994). The entire intracellular domain of the murine receptor (amino acids 780 ± 1122) (Tek IC ) was fused in-frame to the DNA binding domain of the Escherichia coli (E. coli) LexA transcriptional activator and this resulted in constitutive tyrosine phosphorylation of the fusion protein ( Figure 1a).…”
Section: Identi®cation Of a Novel Tek Binding Protein Dok-rmentioning
confidence: 99%
“…As an approach to identify molecules that are involved in Tek signaling pathways, we have used the yeast twohybrid system to ®nd proteins that can interact with the intracellular domain of Tek in a phosphotyrosinedependent manner (Fields and Song, 1989;Chien et al, 1991;O'Neill et al, 1994;Pandey et al, 1994). The entire intracellular domain of the murine receptor (amino acids 780 ± 1122) (Tek IC ) was fused in-frame to the DNA binding domain of the Escherichia coli (E. coli) LexA transcriptional activator and this resulted in constitutive tyrosine phosphorylation of the fusion protein ( Figure 1a).…”
Section: Identi®cation Of a Novel Tek Binding Protein Dok-rmentioning
confidence: 99%
“…The N-terminally truncated EF-1a-like polypeptides of eRF3, referred to as eRF3* (Ito et al+, 1998a), of S. pombe, S. cerevisiae, Xenopus laevis, and humans are known to bind to eRF1 both in vivo and in vitro (Stansfield et al+, 1995;Zhouravleva et al+, 1995;Ito et al+, 1998a)+ To further map the eRF1-binding site(s), S. pombe eRF3 was truncated by KpnI restriction enzyme at amino acid position 481, splitting into two fragments, eRF3⌬C and eRF3C (Fig+ 1)+ The ability of these polypeptides to interact with S. pombe eRF1 was examined by the GAL4-based two-hybrid system (Fields & Song, 1989;Chien et al+, 1991), as described previously (Ito et al+, 1998a)+ eRF1 and eRF3 polypeptides were cloned in-frame downstream of the GAL4 activation (ad) and binding (bd) domains, respectively, and the resulting plasmids were transformed in different pair-wise combinations into S. cerevisiae host strain HF7c (Feilotter et al+, 1994)+ (Note that the reciprocal fusions between release factors and ad/bd vectors were also tested in all two-hybrid analyses shown here, which gave essentially the same result+) The HF7c yeast strain contained a reporter gene, HIS3, under the control of GAL4-responsive elements, and an in vivo protein-protein interaction enabled the reporter transformant to grow on histidine-free minimal medium+ This two-hybrid assay indicated that the C-terminal segment eRF3C (amino acid positions 482-662) bound eRF1 (see Fig+ 4A, sample 1) similarly to eRF3* (positions 212-662), whereas the N-terminal segment eRF3⌬C (positions 1-481) and eRF3*⌬C (positions 212-481) did not (data not shown; see Fig+ 1)+ To confirm the interaction of truncated eRF3 polypeptides with eRF1 in vitro, the eRF3 segments were fused to their N-termini with glutathione S-transferase (GST), as described previously (Ito et al+, 1998a), and immobilized onto glutathione-agarose beads for the pull-down analysis+ S. pombe eRF1 was tagged at its N-terminus with a hexa-histidine sequence and purified by affinity to nickel-agarose beads (see Materials and Methods)+ The resin with bound GST-eRF3 polypeptides were incubated with purified His 6 -eRF1 and then washed to remove nonspecific proteins+ Bound proteins were eluted and analyzed by Western blotting to stain the eRF1-bearing histidine tag with an Ni-NTA-horseradish peroxidase conjugate+ When the eRF1 and eRF3 derivatives were mixed, immobilized eRF3, eRF3*, and eRF3C efficiently precipitated eRF1, as shown in the SDS-polyacrylamide gel analysis (PAGE) (Fig+ 2B, lanes 6, 8, and 10), whereas immobilized eRF3⌬C and eRF3*⌬C did not (Fig+ 2B, lanes 7 and 9)+ These results indicated that the eRF1-binding site on eRF3 resides in positions 482-662 and that the G domain is not involved in the binding+ It is known that S. pombe eRF3 and eRF3* are able to restore growth of the temperature-sensitive eRF3 strain, gst1-1 (Kikuchi et al+, 1988) by intergeneric complementation (Ito et al+, 1998a)+ Neither of the truncated polypeptides, eRF3C or eRF3⌬C, however, restored the viability of the gst1-1 strain (data not shown)+…”
Section: Binding Of Erf1 To the C-terminal Domain Of S Pombe Erf3mentioning
confidence: 99%
“…With the yeast two-hybrid screen, students perform an experiment in which they identify novel protein-protein interactions [8]. Such a research-oriented experience has been well-documented as an effective approach to learning [9,10] and has been previously adapted in the classroom setting using yeast two-hybrid [11].…”
Section: Introductionmentioning
confidence: 99%